3D numerical analysis on wind and rain induced oscillations of water film on cable surface. Issue 176 (May 2018) - Bi, J.H.; Guan, J.; Wang, J.; Lu, P.; Qiao, H.Y.; Wu, J.
Abstract: Rain and wind induced vibration (RWIV) of cable on cable-stayed bridges is a three-dimensional phenomenon. However, previous studies about the numerical analysis on the RWIV mostly concentrate in 2D model, because of the complexity of Computational Fluid Dynamics (CFD). In this paper, a 3D equation of water film evolution is established for the first time, based on the lubrication theory, in which the effects of gravity, water film surface tension, aerodynamic lift and the vibration of the cable are considered. By solving the equations using Finite Difference Method (FDM), the water film thickness variation time history curves at every point on the cable surface are obtained. The results show that an upper rivulet forms throughout the cable along with the axial direction periodically and the phenomenon of axial flow of water film is very obvious. The locations of the upper rivulet are different at every section along with the axial direction at the same moment. The dominant frequency of the evolution of water film is close to the nature frequency of cable. Graphical abstract: Image 1 Highlights: The 3D equation of the evolution of water film is presented. The finite difference method to solve the coupled equations of RWIV is given. Upper rivulets oscillate periodically in circumferential directions. Results of axial flow of water film is obtained.